2022
DOI: 10.7759/cureus.21669
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Early Versus Late Intubation in COVID-19 Patients

Abstract: Background The implications of intubation timing in COVID-19 patients remain highly debatable due to the scarcity of available evidence. Objectives Our study aims to assess the clinical characteristics and outcomes of COVID-19 patients undergoing early intubation compared to those undergoing late intubation. Methods This is a single-center retrospective study of adult COVID-19 patients admitted between March 1, 2020 and January 10, 2021. Early intubation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…Though the risk of death in the present ICU cohort was high (42% overall and 78% in those who received mechanical ventilation) it was consistent with other cohorts from early in the pandemic. 2123 Studies of later cohorts have reported mortality rates of 50% or lower in those with COVID-19 who are intubated, which is consistent with the reduction in mortality rate observed over time at The University of Michigan Health West. 22,23 Though the present results may be generalizable to other relatively small community health systems that provide the majority of health care in the USA, we should acknowledge other factors that may affect external validity.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Though the risk of death in the present ICU cohort was high (42% overall and 78% in those who received mechanical ventilation) it was consistent with other cohorts from early in the pandemic. 2123 Studies of later cohorts have reported mortality rates of 50% or lower in those with COVID-19 who are intubated, which is consistent with the reduction in mortality rate observed over time at The University of Michigan Health West. 22,23 Though the present results may be generalizable to other relatively small community health systems that provide the majority of health care in the USA, we should acknowledge other factors that may affect external validity.…”
Section: Discussionsupporting
confidence: 63%
“…2123 Studies of later cohorts have reported mortality rates of 50% or lower in those with COVID-19 who are intubated, which is consistent with the reduction in mortality rate observed over time at The University of Michigan Health West. 22,23 Though the present results may be generalizable to other relatively small community health systems that provide the majority of health care in the USA, we should acknowledge other factors that may affect external validity. The present cohort consisted largely of obese, unvaccinated patients during the earlier phase of the pandemic.…”
Section: Discussionsupporting
confidence: 63%
“…Therefore, most patients already had severe ARDS once placed on mechanical ventilation. However, studies on timing to intubation did not affect mortality (Papoutsi et al, 2021;Al-Tarbsheh et al, 2022). This may be due to self-injurious lung injury in spontaneously breathing patients, that is akin to ventilator induced lung injury (Weaver et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This has placed a heavy burden on the healthcare system around the world. Earlier studies and observations, including one metanalysis [ 8 ], did not reveal a significant difference in mortality comparing early intubation to late intubation strategy in a COVID-19 patient, taking into consideration that most of the early intubated group were defined as patients who required intubation within 24 hours of hospital admission [ 9 , 10 ]. In our cohort, we defined the early intubation group as patients who require intubation within 72 hours of hospital admission to evaluate the mortality outcome and the mortality predictor of early and late intubation groups.…”
Section: Introductionmentioning
confidence: 99%